Políticas públicas e patrimônio nos Casarões da Sete - Fernandes, Flávia de Oliveira (2021)
This master thesis analyzes the process of construction and deconstruction of the immovable historical heritage discourses of Manaus through Casarões da Sete, an architectural complex of historic mansions demolished between 2008 and 2010 when inserted in the works of PROSAMIM I for the construction of Parque Senador Jefferson Peres and the Cultural Events Hall of the Secretaria de Estado de Cultura, located on Sete de Setembro Avenue, downtown district of the city of Manaus, capital of the State of Amazonas. It is noteworthy that heritage is born in modernity, and over time it has passed and continues to go through different conceptual reformulations. We raise, then, the matter of classifications that select what enters or not in the list of goods to be preserved, which consequently reaches the discursive scales such as values, patrimonial policies, power relations and the duality between theory and effective practice. A look at material and immaterial heritage is launched, in the sense of what is still the importance of this heritage of stone and lime within a contemporary public policy. We base this case study on interdisciplinarity and a qualitative approach, we use documentary and bibliographic sources such as international preservation letters, national, state and municipal legislation, newspapers, periodicals, iconography, other research on the theme of heritage in Manaus and in other regions, the process available at IPHAN-AM for the demolition of Casarões; in addition to field research such as data collection, photographic record with drone and interview. From the analysis, we emphasize that in Manaus heritage policies are marked by selectivity and ephemerality, where the focus is often on erasing the appearance of disorderly growth and the references are always sought at Belle Époque, highlighting the field of power relations.